The use of the cochineal insect, Dactylopius tomentosus Lamarck, as a biological control agent for the invasive alien thistle cholla, Cylindropuntia pallida (Rose) F.M. Knuth in South Africa - Zozo, Ekhona (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Cylindropuntia pallida (Rose) F.M. Knuth (Cactaceae) is an invasive alien plant in South Africa indigenous in the southern U.S.A. and Mexico. Large infestations of this species can be found in the Kalahari and arid Karoo regions of South Africa, which is also present in Namibia. Because it is a very spiny cactus, dense infestations have a negative impact on agriculture and natural ecosystems. This cactus has become naturalised to the extent that eradication is impossible and the negative impacts are steadily increasing due to its increasing distribution and density. The cochineal insect, Dactylopius tomentosus Lamarck (Dactylopiidae), is native in Mexico and parts of North America, such as Texas, Arizona, and New Mexico in the U.S.A. This cochineal species is highly specialized and associated only with Cylindropuntia species, a group of cacti that are primarily restricted to the same areas. It has been introduced into Australia and South Africa as a biological control agent to control various invasive alien Cylindropuntia species. This cochineal species has several biotypes specific to certain Cylindropuntia species hosts. A biotype is a clade that cannot be differentiated morphologically from others but has different host ranges and impacts depending on the host plant species. Included amongst biotypes that have been released in South Africa are D. tomentosus 'imbricata' and D. tomentosus 'cholla' for the biological control of Cylindropuntia imbricata (Haw.) F.M. Knuth (Cactaceae) and Cylindropuntia fulgida (Engelmann) F.M. Knuth var. mamillata (Schott ex Engelmann) Backeb. (Cactaceae), respectively. These biotypes have resulted in both host plants being under substantial control in South Africa. The first part of this thesis evaluated which of the two D. tomentosus biotypes already in use in South Africa could be an effective biological control agent for C. pallida. This was done by assessing the fitness of the cochineals on the three cactus species and assessing the impact that each of the cochineals has on each of the target weed species. Should these biotypes prove ineffective, there is a third biotype, namely D. tomentosus 'californica var. parkerii', which researchers in Australia have worked on and have found to be suitably host-specific for release in Australia and suitably damaging to C. pallida in that country. Therefore, this new biotype could be released in South Africa if it is required. Sexually compatible biological control agents, especially those closely related and occurring in close spatial proximity to one another, may interbreed and the impacts of this hybridisation are difficult to predict. It is important to understand the outcomes of the hybridisation of cochineal because it can affect the impact of the biological control agents and thus the control of the target weed. The second part of this thesis investigated the impacts of the hybridisation of the two cochineal biotypes by assessing the damage the agents would have on the target weed, and on C. imbricata and C. fulgida var. mamillata, in the presence of one or both cochineal biotypes. The 'cholla' biotype performed better on C. pallida than the 'imbricata' biotype, but neither biotype could control C. pallida to an extent similar to the control they provide for their respective target weeds, C. imbricata and C. fulgida var. mamillata. Both the 'cholla' biotype and hybrids of the two biotypes of cochineal were effective at killing C. pallida when both C. imbricata and C. fulgida var. mamillata were also present. This suggests that the 'cholla' or hybrids may be effective at controlling C. pallida when either C. imbricata or C. fulgida var. mamillata are also present in the field due to the high population density of cochineal that results under these circumstances. There are, however, many C. pallida infestations in South Africa where the plant is problematic and is isolated from other Cylindropuntia species, and these populations are unlikely to be controlled by the 'cholla' biotype or the hybrids. Neither of the cochineal biotypes that are used for biological control in South Africa are suitably damaging to C. pallida to warrant their use as biological control agents for this species. Dactylopius tomentosus 'californica var. parkerii' is therefore recommended for release based on its host-specificity and impact to C. pallida in Australia.
Keywords: Cochineal insect; Thistles Biological control -- South Africa; Alien plants -- South Africa; Invasive plants -- South Africa; Cactus -- South Africa; Biological assay